MATEMATIKA SPIRITUAL: EKSPLORASI KONSEP PAHALA DALAM AJARAN ISLAM - Makmur, Makmur (Dahzain Nur, 2025)
This study aims to explore how every good deed can yield abundant rewards within the framework of spiritual mathematics. The research adopts a literature review (library research) approach by analyzing various religious texts related to the topic. The findings reveal that every good deed is rewarded with at least tenfold returns, but in some cases, it may yield none, depending on the belief that Allah swt grants rewards based on specific criteria and divine principles. Although mathematically, equations like 1 + 1 = 10 or 1 + 1 = 0 may seem illogical, in the spiritual context, such outcomes are grounded in the logic of sincerity, divine approval, compassion, blessings, and abundance non-material consequences of righteous actions. The belief that small acts can lead to significant outcomes is a core teaching in Islamic spirituality. Understanding this concept can inspire and motivate individuals to perform more good deeds with the conviction that every positive action can bring far-reaching and meaningful impacts, both personally and socially.